A study on the demand for family takaful and life insurance: a comparative study in Malaysia (2000 - 2013) / Amirah Liyana Aminuddin - Aminuddin, Amirah Liyana (2014)
There are two types of life insurance offered in Malaysia which are conventional life insurance and Islamic family takaful. It was reported that the net contribution for family takaful cannot beat the premium for life insurance for the period of 2000 until 2013. Thus, it can be seen that family takaful market still lags behind the life insurance market. Therefore, this study is conducted in order to examine the economic determinants that will influence the demand for family takaful and comparing with the demand for life insurance. Macroeconomic environment has an important influence on family takaful and life insurance since economic environment is said to have a profound effect on the growth of the insurance industry. Hence, this research project will examine the takaful market and insurance market in Malaysia by using data obtained from Bank Negara Malaysia for the period of 2000 to 2013. For the purpose of this research project, regression methodology is adopted in order to obtain and analyze the findings. The findings of this research project indicate that three variables namely income and savings rate have significant positive relationship with the demand for family takaful while interest rate have a significant negative relationship with the demand for family takaful. However, income is said to have a significant positive relationship with the demand for life insurance and savings rate have a significant negative relationship with the demand for life insurance. For the demand for life insurance, interest rate is found to be insignificant with the demand for life insurance.